The Book of Exodus : a Biography - Baden, Joel S., 1977- (Princeton University Press, 2019)
An essential biography of one of the Bible's most powerful and inspiring booksExodus is the second book of the Hebrew Bible, but it may rank first in lasting cultural importance. It is here that the classic biblical themes of oppression and redemption, of human enslavement and divine salvation, are most dramatically expressed. Joel Baden tells the story of this influential and enduring book, tracing how its famous account of the Israelites' journey to the promised land has been adopted and adapted for millennia, often in unexpected ways. Baden draws a distinction between the Exodus story and the book itself, which is one of the most multifaceted in the Bible, containing poems, law codes, rituals, and architectural plans. He shows how Exodus brings together an array of oral and written traditions from the ancient Middle East, and how it came to be ritualized in the Passover Seder and the Eucharist. Highlighting the remarkable resilience and flexibility of Exodus, Baden sheds light on how the bestowing of the Torah to Moses on Mount Sinai divided Jewish and Christian thinkers, on the importance of Exodus during the Reformation and the American Revolution, and on its uses in debates for and against slavery. He also traces how the defining narrative of ancient Israel helped to define Mormon social identity, the American civil rights movement, and liberation theology. Though three thousand years old, the Exodus--as history, as narrative, as metaphor, as model--continues to be vitally important for us today. Here is the essential biography of this incomparable spiritual masterpiece.